Odpowiedzi

Najlepsza Odpowiedź!
2010-01-24T20:58:39+01:00
Wykonaj działanie.
a) -(x+4)+(x-5) = -x-4+x-5 = -9
b) 1-(t+p)-(t-2) = 1-t-p-t+2 = 3-2t-p
c) -(-y+2)+(-2y-4) = y-2-2y-4 = -y-6
zapisz jak najproszczj postaci
a) -(kx+ny)-(3kx+2ny)+(5kx-3ny) = -kx-ny-3kx-2ny+5kx-3ny = kx-6ny
b) (2ab+a+3)-(3ab-a+3) = 2ab+a+3-3ab+a-3 = -ab+2a
1 5 1
2010-01-24T20:59:38+01:00
A) -(x+4)+(x-5)=-x-4+x-5=-9
b) 1-(t+p)-(t-2)=1-t-p-t+2=3-2t-p
c) -(-y+2)+(-2y-4)=y-2-2y-4=-y-6
1 3 1
2010-01-24T21:00:09+01:00
1
a-x-4+x-5=-9
b1-t-p-t+2=3-p-2t
c y-2-2y-4=-6-3y
2
a-kx-ny-3kx-2ny+5kx-3ny=kx-6ny
b 2ab +a +3 - 3ab+a-3=-ab+2a